Transfer and Vascular Effect of Endothelin Receptor Antagonists in the Human Placenta. Issue 3 (March 2020) - Hitzerd, Emilie; Neuman, Rugina I.; Broekhuizen, Michelle; Simons, Sinno H.P.; Schoenmakers, Sam; Reiss, Irwin K.M.; Koch, Birgit C.P.; van den Meiracker, Anton H.; Versmissen, Jorie; Visser, Willy; Danser, A.H. Jan
Abstract : Increasing evidence suggests a role for the ET (endothelin) system in preeclampsia. Hence, blocking this system with endothelin receptor antagonists (ERAs) could be a therapeutic strategy. Yet, clinical studies are lacking due to possible teratogenic effects of ERAs. In this study, we investigated the placental transfer of ERAs and their effect on ET-1-mediated vasoconstriction. Term placentas were dually perfused with the selective ETA R (ET type A receptor) antagonists sitaxentan and ambrisentan or the nonselective ETA R/ETB R antagonist macitentan and subsequently exposed to ET-1 in the fetal circulation. ET-1 concentration-response curves after incubation with sitaxentan, ambrisentan, macitentan, or the selective ETB R antagonist BQ-788 were also constructed in isolated chorionic plate arteries using wire-myography, and gene expression of the ET-system was quantified in healthy and early onset preeclamptic placentas. At steady state, the mean fetal-to-maternal transfer ratios were 0.32±0.05 for sitaxentan, 0.21±0.02 for ambrisentan, and 0.05±0.01 for macitentan. Except for BQ-788, all ERAs lowered the response to ET-1, both in the perfused cotyledon and isolated chorionic plate arteries. Placental gene expression of ECE-1, ETA R, and ETB R were comparable in healthy and preeclamptic placentas, while ET-1 expression was higher in preeclampsia. Our study is the first to show direct transfer of ERAs across the term human placenta. Furthermore, ETA R exclusively mediates ET-1-induced constriction in the fetoplacental vasculature. Given its limited transfer, macitentan could be considered as potential preeclampsia therapy. Extending knowledge on placental transfer to placentas of preeclamptic pregnancies is required to determine whether ERAs might be applied safely in preeclampsia. Abstract : Supplemental Digital Content is available in the text.